Simulações de Monte Carlo para o estudo da dosimetria interna em imagens de medicina nuclear de mulheres grávidas - Dartora, Caroline Machado (2017)
The statistical nature of the physical process involved in Nuclear Medicine exams makes the use of Monte Carlo methods an useful tool for deposited energy and absorbed dose calculations on organs, mainly for risk-benefits assessment. Pregnant are important target for risk-benefit assessment, due the fetus exposure to radiation. Nuclear Medicine exams may generate fetus dose, either by irradiation due to maternal organs, or by activity that crosses the placenta and accumulates in fetus. Usually, both internal dosimetry estimation software and virtual anthropomorphic simulators are proprietary. The aim of this research is to investigate the use of GATE (Geant4 Application for Emission Tomography) application of Monte Carlo method on internal dosimetry calculation in simulated Nuclear Medicine image exams in pregnant woman. First, an evaluation of the use of GATE was performed to build dose maps with simple geometries. An evaluation of the radiation interaction behavior with respect to available GATE source types of configuration of single photon (99mTc) and positrons (18F) emitters was also performed. Dose estimation on a fetus was performed by simulation of a [18F] FDG distribution in a virtual 24-week pregnant woman simulator, Katja, with data based on literature. It was evaluated the impact on fetal dose of the mother bladder uptake of , placenta uptake, maternal organs irradiation and dose generated due to the uptake only in the fetus. The total estimated dose for a fetus on 24 weeks was 0.0122 mGy/MBq, in agreement with published data. Several individual dose contributions in the fetus that are not commonly found in the literature, such as the contribution due to the bladder (13%) and placenta (0.53%) were obtained. The contribution in total fetal dose of the activity only in the organs of the fetus was analyzed, resulting in 3.8%, where 56% is due only to positron emitted by the source. In conclusion, GATE generates dose maps that can be used as a method of dose estimation in pregnant women in MN scans, giving detailed information about the individual contributions of maternal organs uptake.